Pharmacoeconomic and associated cost savings among women who were prescribed systemic conjugated estrogens therapy compared with those without menopausal therapy. Issue 5 (May 2018) - Tang, Wing Yu; Grothe, Dale; Keshishian, Allison; Morgenstern, Diana; Haider, Seema
Abstract: Objective: To explore changes in healthcare costs among postmenopausal women in a commercial population who were prescribed conjugated estrogens for menopausal symptoms. Methods: Using the MarketScan dataset from April 1, 2008 through September 30, 2012, postmenopausal women aged ≥45 years, who were prescribed conjugated estrogen tablets (Premarin), were identified. A comparative cohort of postmenopausal women with vasomotor symptoms without any menopause therapy was also identified. Women included were required to have continuous medical and pharmacy benefits for 6 months before and 12 months after index date, with baseline characteristics compared using chi-square and t tests. The 6 and 12-month change (difference in follow-up and baseline costs) in direct healthcare costs was calculated and a difference-in-differences model was used to compare the incremental change at 6 and 12 months in healthcare costs between the cohorts, adjusting for demographic and clinical characteristics. Results: The study included 1, 404 women who were prescribed conjugated estrogens, and 3, 096 untreated women. Women prescribed conjugated estrogens were significantly younger (52 vs 54 years; P  < 0.0001) and had a lower Charlson comorbidity index score (0.29 vs 0.41; P  < 0.001) compared with the untreated women. After adjusting for baseline characteristics, women treated with conjugated estrogens showed a greater difference in the change in total healthcare costs (−$1, 601 vs −$503; P  = 0.044), including inpatient stay costs (−$1, 431 vs −$28; P  < 0.0001), between the baseline and follow-up periods compared with untreated women. Conclusions: Women who were prescribed oral conjugated estrogens had a significantly greater reduction in healthcare costs after treatment initiation compared with untreated postmenopausal women. Abstract : Supplemental Digital Content is available in the text